Micro-mechanics of imperfect interface between dissimilar materials with micro-structures - Liu, Yuquan (Nanyang Technological University, 2023)
The present study investigates three distinct types of imperfect interfaces between dissimilar materials, each exhibiting unique micro-structures. The first type of interface is characterized by evenly distributed micro-cracks and is modeled as spring-like. The effective property stiffness of this interface, denoted by K, is evaluated through the use of Finite Element Method (FEM), Self-Consistent Method (SCM), and analytical solution techniques. The analytical solution uncovers an equivalence relation between stiffness K and energy release rate of cracks, providing insights into the behavior of the interface damaged by micro-cracks.